PEMANFAATAN ARTIFICAL INTELLIGENC DALAM INOVASI KATALOG MARKETING PRODUK OLEH-OLEH JAMBI - Mei Riska Elen; Yuli Setiyawati (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2023)
In the 5.0 era, the focus is on human mindset based on technology, one of which is utilizing marketing innovation to increase economic growth in Indonesia. Development of a computer system that is capable of being run by humans in completing life tasks at the financial level of the economy, namely being able to apply an Artificial Intelligence (AI) system which is unique because it is able to work according to certain computer system programming algorithms, programming algorithms are an artificial intelligence framework for processing various types of data . AI has many benefits in various aspects of life, especially in the economic aspect in Indonesia. Economic growth in Indonesia has experienced a decline due to Covid-19, one of which is Jambi Province which has experienced a decline in economic growth. Based on data obtained from the Bank Indonesia Representative for Jambi Province, it shows that economic growth in Jambi City in 2019 was 4.35%, in 2020 it changed to -0.51% from 11,000 MSMEs during the Covid-19 period which resulted in bankruptcy. In 2021, 8,300 MSMEs were registered in Jambi City, amounting to 3.69%. In 2022 it will increase to 5.13% with the number of MSMEs now reaching more than 60,000, with an average of dominant businesses in the culinary food and beverage sector. With the increase in MSME players every year, marketing competitiveness is getting stronger. This requires MSME players to be able to adapt to keep up with the times, while consumer behavior currently prefers to shop online considering the time and affordability of cheap prices compared to shopping in person. The research method used is a qualitative descriptive approach. Data collection techniques were carried out through observation, interviews and news on the WEB. This research uses the Manual Data Analysis Procedure (MDAP) analysis technique to analyze transcription data from interviews that have been obtained directly from the field by informants who follow the purposive sampling technique. These findings use the theory of utilizing AI and business marketing innovations which make it easier for producers and consumers to obtain the right profits.